An economic analysis of high milk somatic cell counts in dairy cattle in Chiang Mai, Thailand - Dejyong, Tosapol; Chanachai, Karoon; Immak, Nathawit; Prarakamawongsa, Tippawon; Rukkwamsuk, Theera; Tago Pacheco, Damian; Phimpraphai, Waraphon (Frontiers in Veterinary Science, 2022)
Mastitis in dairy cattle can lead to significant financial losses due to a reduction in milk yield, the withdrawal period after treatment when milk cannot be sold, and an increase in somatic cell count (SCC) which can reduce the milk’s per Litre commercial value. Dairy cooperatives point at high SCC problems as an important factor leading to suboptimal levels of milk quantity and quality. This study aims at describing farm characteristics and milking practices associated with high SCC, identifying risk factors, and assessing the economic loss due to high SCC in three dairy cooperatives in Chiang Mai, Thailand. A cross sectional study was conducted on 208 dairy cattle farms from July to September 2018. Structured interviews were conducted to collect the data. Univariate and multivariate analysis were performed to determine the degree of association between factors and high SCC. A retrospective cost assessment of high SCC was conducted to estimate the losses in affected farms, and two potential coping strategies were assessed: 1) culling, 2) treating the cow. More than 12% of farms had high SCC (SCC > 500,000 cells/ml). Inappropriate vacuum pressure and inappropriate pulsation rate of milking machines were identified as significant risk factors according to the multiple logistic regression (P < 0.01). Both factors can decrease the natural protection of teat tissue, increasing the likelihood of bacterial infection. The average economic loss of high SCC in affected farms was 557 USD for a three-month period. When comparing response strategies (i.e., treatment vs culling), treating the affected cow was found to be more cost-effective. With a probability of successful treatment of 54%, treating an affected cow leads to 1,158.7 USD in gains over three years (vs doing nothing). The results of this economic analysis can be used to advocate to cooperatives the value of veterinarians and for investigating and treating cases of mastitis.